Meshkwajisewin: Paradigm Shift - Maureen Anne Matthews; Roger Roulette; James Brook Wilson (Religions, 2021)
In 2012, the Manitoba Museum began the development of an exhibit called “We Are All Treaty People”. Mindful of recent scholarship on animacy and the ontological turn in museum ethnography, this paper examines how this exhibit reversed decades of practice regarding ceremonial artefacts. Twelve pipes, formerly removed from view because of their ceremonial status, have now, as celebrated animate entities, become teachers in a collaboratively developed exhibit about treaties. They will work to educate thousands of visitors, many of them Indigenous children who visit the museum annually. The exhibit was imagined, shaped, and made possible by the Elders Council of the Association of Manitoba Chiefs and the Treaty Relations Commission of Manitoba who treat the pipes as active social partners and, from the outset, intended that the pipes would boldly instantiate Indigenous agency in treaty making. The relational world of the pipes has increased exponentially since they have become public actors in the museum, and more importantly, they have formed deep bonds with the school children and Elders of the community of Roseau River First Nation. They go to the school yearly to be celebrated, sung to, feasted, smoked, and honoured and return to the museum restored and ready for their newfound educational and diplomatic work.